Evaluation of the association between lower urinary tract symptoms and erectile dysfunction, considering its multiple risk factors - Rhoden, Ernani Luis (2008)
Aim. To investigate the relationship between lower urinary tract symptoms (LUTS) and erectile dysfunction (ED), while considering multiple risk factors for ED, including an anthropometric evaluation of central obesity. Methods. A cross-sectional study was carried out with 192 consecutive male subjects ( 40 years old). Conditions clearly associated with ED, other than obesity and age, were considered exclusion criteria. Men were evaluated routinely for clinical history, received a physical examination, and were subjected to blood analysis for fasting serum glucose, lipid profile, and serum testosterone. Patients with previous known history of diabetes mellitus or hypertension were excluded. Anthropometric measures taken included body mass index (general obesity) and waist circumference, waist-hip index, and sagittal abdominal diameter (visceral obesity). Analyses were performed using bivariate and multivariate models (multiple logistic regression). Age, education, alcohol consumption, smoking, sedentary lifestyle, fasting blood glucose level, dyslipidemia, hypogonadism, general obesity, and visceral obesity were taken into account as potential confounding factors. Main Outcome Measures. All men completed the International Index of Erectile Function and International Prostate Symptom Score (IPSS). Results. IPSS scores were low, intermediate, and high in 89 (46.4%), 76 (39.6%), and 27 (14.1%) men, respectively. Overall IPSS scores were significantly associated with ED (P = 0.002). In addition, an association between the severity of ED and LUTS was observed (P = 0.008). The mean quality of life assessment in the IPSS revealed a statistically significant difference between individuals with varying degrees of ED (P = 0.008). The logistic regression analyses showed that IPSS scores and ED remained independently associated even after the control for confounding factors (odds ratio = 1.07, 95% CI = 1.02–1.13, P = 0.01). Conclusion. This study suggests that LUTS are independently associated with ED, taking into account various risk factors for ED, including visceral obesity.